Are students gender-neutral in their assessment of online teaching staff?. Issue 5 (19th July 2021) - Wong, Jennifer S.; Bouchard, Jessica
Abstract: The scores from student evaluation forms are often used to construct assessments about the quality and effectiveness of course instruction. These assessments, in turn, can have serious professional impacts on instructors with respect to future course assignments, grants, promotion and hiring decisions. Previous research suggests that scores from student evaluations can be significantly predicted by factors other than teaching quality, in particular, the gender of teaching staff. However, most existing research is challenged by logistical constraints of separating gender from teaching quality in face-to-face courses. The goal of the current study was to examine gender-neutrality in students' assessments of teaching assistants, by manipulating perceived teaching assistant gender for an online course. Using a mixed methods approach across nine semesters in which teaching assistants posed as both male and female, findings from 232 students suggest mixed evidence concerning gender bias in evaluations of teaching assistant performance. Highlights include no significant differences for the overall mean performance scores between the perceived male versus perceived female subgroups; individual item analysis suggests that students were more likely to rate the perceived male teaching assistant as having high expectations and the course as having a more challenging workload. Limitations and directions for future research are discussed.